TOURIST SATISFACTION AS A MEDIATOR OF THE INFLUENCE OF PRICE AND FACILITIES ON VISITING DECISIONS TO LAKE LINGKAT - Haryono, Gampo; Sukmawati, Dina (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
Tourism is a modern industry that contributes significantly to economic growth through employment, income generation, and improvements in living standards while activating other sectors in the host region. This study employs a quantitative descriptive approach with a survey method to collect primary data from respondents. The research was conducted at Lake Lingkat, one of the leading natural tourist destinations in Kerinci Regency. The choice of Lake Lingkat as a research location is due to its increasing visitor numbers and natural attraction. The validity tests on all variables Ticket Price, Tourist Facilities, Visiting Decisions, and Tourist Satisfaction show valid results, and the reliability tests indicate all instruments are reliable with Cronbach’s Alpha values above the 0.60 threshold. The findings of the study are as follows: (1) Ticket Price does not have a direct effect on Visiting Decisions; (2) Tourist Facilities have a direct influence on Visiting Decisions; (3) Ticket Price and Tourist Facilities do not directly affect Tourist Satisfaction; (4) Tourist Satisfaction does not have a direct influence on Visiting Decisions; (5) Ticket Price and Facilities indirectly affect Visiting Decisions through Tourist Satisfaction, confirming that Tourist Satisfaction acts as a mediating variable.